The Role of Schools in Fostering The Entrepreneurial Spirit of Students in Senior High School 8 Surakarta - Sephianingrum, Dinda Putri; Ulfatun, Titik (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this research is to 1) Describe the role of schools in fostering the entrepreneurial spirit of students at SMA Negeri 8 Surakarta. 2) Describe the efforts of teachers in the learning process of entrepreneurship subjects at SMA Negeri 8 Surakarta. 3) Describe the entrepreneurial spirit of students at SMA Negeri 8 Surakarta. The research design used in this research is a case study in qualitative research. In this study there are several sources that will be the subject of research which include the deputy curriculum, entrepreneurship subject teachers, and students of SMA Negeri 8 Suarakarta. In this study, observation, interviews, and documentation as data collection methods. This research uses source triangulation to ensure the accuracy of the data. The result of this research is that the school provides facilities for students to develop their entrepreneurial potential through practice in daily entrepreneurship learning and the Gelar Karya program by the school to realize the Pancasila Student Profile Strengthening project at SMA Negeri 8 Surakarta or with the classmeeting event formed by the school organization.